ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA KEPEMILIKAN DAN PENYALAHGUNAAN SENJATA REPLIKA AIRSOFT GUN - Faizal Roy Gading; Dessy Artina; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The State of Indonesia is a state of law (recht staats), so every person who commits a crime must be held accountable for his actions through the legal process. supervision of the circulation and use of firearms is indicated in the Emergency Law of the Republic of Indonesia Number 12 of 1951 explaining who who without the right of entering into Indonesia makes, receives, tries to obtain can be sentenced to death or life imprisonment or a maximum prison sentence twenty years. The purpose of this thesis, namely: First, to find out the implementation of criminal acts of ownership and misuse of Airsoft Gun replica weapons. Second, to find out criminal liability for the possession and misuse of Airsoft Gun replica weapons.This type of research can be classified as a type of normative legal research, which is a study conducted by examining literature or secondary data. In this study, the analysis that will be used by the writer is a qualitative analysis of data analysis by not using statistics or mathematics or the like.From the results of research and discussion it can be concluded that, criminal liability for ownership and misuse of Airsoft Gun can be imposed on perpetrators both individuals, legal entities / corporations. Second Misuse of Airsoft Gun ownership can be qualified as a criminal offense if it meets the elements of a criminal act regulated in criminal law. Like cases of threats, bank shootings and robberies in Central Java by using airsoft guns can be categorized as criminal acts and are subject to Article 1 Paragraph (1) Emergency Law Number 12 of 1951. These laws can be applied because of the characteristics and functions of Airsoft Gun that are not much different from a firearm. Misuse of Airsoft Gun can be considered a criminal offense if its use is not in accordance with its intended use, not a misuse, but because of a criminal offense, for example, a robbery in the Criminal Code regulated in Article 362 of the Criminal Code. The suggestions that can be taken include remembering the regulation of aroscope gun is very limited, while the forms of criminal use of Airsoft Gun vary greatly, then the government should make specific rules about ownership and misuse of Airsoft Gun along with sanctions.Keywords: Responsibility-Ownership-Airsoft Gun Replica Weapons.